An in silico model predicts the impact of scaffold design in large bone defect regeneration. (June 2022) - Perier-Metz, Camille; Cipitria, Amaia; Hutmacher, Dietmar W.; Duda, Georg N.; Checa, Sara
Abstract: Large bone defects represent a clinical challenge for which the implantation of scaffolds appears as a promising strategy. However, their use in clinical routine is limited, in part due to a lack of understanding of how scaffolds should be designed to support regeneration. Here, we use the power of computer modeling to investigate mechano-biological principles behind scaffold-guided bone regeneration and the influence of scaffold design on the regeneration process. Computer model predictions are compared to experimental data of large bone defect regeneration in sheep. We identified two main key players in scaffold-guided regeneration: (1) the scaffold surface guidance of cellular migration and tissue formation processes and (2) the stimulation of progenitor cell activity by the scaffold material composition. In addition, lower scaffold surface-area-to-volume ratio was found to be beneficial for bone regeneration due to enhanced cellular migration. To a lesser extent, a reduced scaffold Young's modulus favored bone formation. Statement of significance: 3D-printed scaffolds offer promising treatment strategies for large bone defects but their broader clinical use requires a more thorough understanding of their interaction with the bone regeneration process. The predictions of our in silico model compared to two experimental set-ups highlighted the importance of (1) the scaffold surface guidance of cellular migration and tissue formation processes and (2) the scaffold material stimulation of progenitor cell activity. In addition, the model was used to investigate the effect on the bone regeneration process of (1) the scaffold surface-area-to-volume ratio, with lower ratios favoring more bone growth, and (2) the scaffold material properties, with stiffer scaffold materials yielding a lower bone growth. Graphical abstract: Image, graphical abstract